2014
DOI: 10.1063/1.4892454
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the recoverable energy storage density and efficiency by utilizing the linear dielectric response in ferroelectric capacitors

Abstract: Articles you may be interested inMeta-aromatic polyurea with high dipole moment and dipole density for energy storage capacitors Appl. Phys. Lett.Mechanical self-confinement to enhance energy storage density of antiferroelectric capacitors J. Appl. Phys. 113, 054101 (2013); 10.1063/1.4790135High field tunneling as a limiting factor of maximum energy density in dielectric energy storage capacitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 21 publications
(29 reference statements)
1
39
0
Order By: Relevance
“…The energy densities and efficiency of the BFSTO films are compared with those of representative lead-based and lead-free material systems reported previously, as displayed in Fig. 3c 1012,2833 . The results evidently show that the energy densities of the BFSTO films are superior to those of other reported lead-free systems (35% over the best BTO-based systems 12 ) and rival the lead-based materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy densities and efficiency of the BFSTO films are compared with those of representative lead-based and lead-free material systems reported previously, as displayed in Fig. 3c 1012,2833 . The results evidently show that the energy densities of the BFSTO films are superior to those of other reported lead-free systems (35% over the best BTO-based systems 12 ) and rival the lead-based materials.…”
Section: Resultsmentioning
confidence: 99%
“…a Discharged energy density and b efficiency of the BFSTO films as a function of the applied electric field. c Comparisons of energy density and efficiency between BFSTO and representative dielectric systems 1012,2833 , showing that the BFSTO films possess the most outstanding energy storage performance. d Energy density and efficiency for x  = 0.60 and 0.75 at an electric field of 2.5 MV cm −1 over 1 × 10 7 charging-discharging cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The energy storage performance of the samples in this study can be expressed by (η, W rev ), for example, (81.3%, 63.7) has been obtained for PZT/AO/PZT opposite double‐heterojunction annealed at 550 °C. The comparison diagram of the energy storage performance is given in Figure for the representative thin films materials, such as polymer thin films, lead‐based thin films, lead‐free thin films . It can be observed that it is difficult to obtain high energy storage density and high efficiency simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…In principle, the energy storage density ( W ) of dielectrics is determined by the integral of the applied electric field ( E ) with respect to the electric displacement ( D ) as W=EdD. Ferroelectric ceramics, which intrinsically possess high polarization, have nowadays been explored as high‐energy‐density candidates, while it is still challenging in terms of the reduction of energy loss and also the enhancement of ultimate breakdown strength. It is commonly accepted that dielectric breakdown is strongly microstructure dependent, and large endeavors have been made regarding the improvement of microstructure through the enhancement of processing technologies .…”
Section: Introductionmentioning
confidence: 99%